Hexane fraction of Prunus japonica thunb. Seed extract enhances boar sperm motility via CatSper ion channel. Issue 2 (February 2023) - Cooray, Akila; Chae, Mee Ree; Wijerathne, Tharaka Darshana; Kim, Dae Geun; Kim, Jeongsook; Kim, Chul Young; Lee, Sung Won; Lee, Kyu Pil
Abstract: Introduction: Mammalian sperm motility is facilitated by flagellar beating, which depends on active ion movement through ion channels and their regulation. Prunus japonica Thunb., also known as oriental bush cherry, is a widely used traditional medicinal plant. However, its significance in improving fertility and sperm quality has not been fully elucidated yet. One of our previous reports revealed that P. japonica seed extract (PJE) can improve human sperm motility through intracellular pH modulation. Aim of the study: The present study was designed to investigate the effects of PJE on boar spermatozoa and potential underlying mechanisms. Materials and methods: Sperm motility changes were examined using a computer-assisted sperm analysis (CASA) system under both capacitated and non-capacitated conditions. Intracellular calcium concentration was measured using either confocal microscopy or a fluorescent microplate reader with Fluo-4AM calcium fluorescent dye. Sperm capacitation-related proteins were analyzed using western blotting. Results: A significant increase in rapid motility, velocity, and linear displacement of sperm was observed in PJE-treated capacitated boar sperm, whereas the effect was insignificant in the non-capacitated counterparts. Intracellular calcium levels were significantly elevated upon PJE treatment (20–100 μg/L) in a concentration-dependent manner. The increase in intracellular calcium levels was inhibited when the sperm were treated with a CatSper (cation channel of sperm) channel inhibitor, 10 μM Mibefradil, indicating the involvement of the ion channel in the PJE modulatory mechanism. In addition, western blotting revealed an increased level of protein phosphorylation (p-tyrosine and p-PKA), which is a hallmark of sperm capacitation. Conclusions: PJE treatment resulted in a combination of increased motility, intracellular calcium concentration, and capacitation, thereby indicating its potential to ameliorate sperm motility parameters and induce capacitation of boar spermatozoa as a result of intracellular calcium elevation via the CatSper channel. Our observations further elaborate ion channel-related underlying mechanisms and show putative implications of the seed extract of traditionally used P. japonica Thunb. in ameliorating sperm quality. Highlights: Prunus japonica Thunb. seed extract improves boar sperm motility parameters. Mechanism of action suggests involvement of CatSper channel. Capacitation of boar sperm can be induced by the seed extract.